The Influence of Internal Social Capital on Serial Creators' Success in Crowdfunding. (31st January 2017) - Skirnevskiy, Vitaly; Bendig, David; Brettel, Malte
Abstract : Interactions between project creators and backers on the crowdfunding platform represent the linchpin of every campaign. However, the resulting internal social capital has received little academic attention. To address this topic, we frame how internal social capital can develop through project track record and how internal social capital can spill over to external online communities. Focusing on the long‐term implications of these manifestations of social capital, we empirically assess whether they can increase funding success beyond a single campaign. We test our hypotheses with two data sets derived from platform and survey sources and find support for the proposed relationships.